Pelatihan Peningkatan Kemampuan Penulisan Artikel Ilmiah Bagi Guru-Guru SMP Negeri Kabupaten Siak Sri Indrapura - Azhar, Fadly; Putra, Riki Apriyandi; Isjoni, M. Yogi Riyantama; Primahardani, Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Writing Scientific Articles is a writing culture carried out by teachers in improving and as a means of self-development to be more professional. Improving mastery of article writing skills for junior high school teachers must always be done because the teacher's understanding is not optimal. The implementation of the workshop method with the purpose of this activity is how to provide stimulation/ stimulation to teachers so that they can get used to compiling a scientific paper starting from class research. Understanding and steps how in terms of implementing PTK, making PTK reports, and producing PTK-based scientific publications. The implementation of this activity was carried out on September 9, 2022 and took place at SMP Negeri 1 Siak Sri Indrapura which is located at Jalan Suak Lanjut, Suak Lanjut, Siak District, Siak Sri Indrapura Regency, Riau Province.